Mechanism of turbidity and hardness removal in hard water sources by using Moringa oleifera - Fahmi, Muhammad Ridwan, Dr.; Nor Wahidatul Azura, Zainon Najib; Pang, Chan Ping; Nasrul, Hamidin, Dr. (Asian Network for Scientific, 2011)
Link to publisher's homepage at http://www.ansinet.com/